Bullets over Petaling Street - Sampson, Yuen; Debbie, Goh; Chen, Han Wei; Irene, Ang (Petaling Jaya, Kuala Lumpur : Juita Viden Media Group, 2014)
This action comedy is about an awkward movie star, who accidentally becomes a Triad leader in an intense election war among 4 main Triads in Petaling Street. Media makes a lot of coverage of this new Triad leader, exposing her for assassination. While she tries to hide from her assassin, she bumps into a restaurant owner Xie Da Xiang who is her ex-boyfriend...
Special features: Production gallery ; Music video.
Director of photography, Wong Tak Fung ; editor, Mak Chee Choong.
Debbie Goh, Chen Han Wei, Irene Ang.
LPF: P13
DVD format, Region ALL, Dolby Digital (5.1 AC3).
In Chinese with optional Malay, English and Chinese subtitles.
Keywords: Comedy films